Pelvic floor therapy program for the treatment of female urinary incontinence in Belize: a pilot study - David E. Rapp; David E. Rapp; Jacqueline Zillioux; Fionna Sun; Marieke Jones; Michelle Little; Michelle Little; Jeanice Mitchell; Jeanice Mitchell (Frontiers Media S.A., 2024)
IntroductionUrinary incontinence (UI) is highly prevalent in low- and middle-income countries (LMIC). Concurrently, the availability of surgical or conservative UI treatments in LMIC is limited.MethodsWe conducted a prospective feasibility study of Belize women with UI treated with pelvic floor physical therapy (PFPT) and education (PFE). Patients received individual PFPT/PFE over 2 days, consisting of biofeedback-enhanced PFMT in addition to behavioral, dietary, and general pelvic education. Patient completed a daily 6-month home regimen including 7 PFMT exercises (total 70 repetitions) comprising both endurance and quick flick exercises. Patients also performed comprehensive dietary and behavioral modification activities. Outcomes were assessed at baseline and 6-months, including validated symptom (ICIQ-FLUTS) and QOL (IIQ-7) questionnaires, and strength testing (PERFECT score, perineometry).ResultsTwenty-eight patients underwent baseline assessment. Four patients were lost to in-person 6-month follow-up, with two of these patients completing subjective assessment only by telephone. The mean (±SD) patient age, BMI, and parity were 50.0 (±10.0) years, 33.2 (±5.8), and 2.8 (±1.5). Provider assessment demonstrated patient comprehension of basic, endurance, and quick flick pelvic floor contractions in 28 (100%), 24 (86%), and 24 (86%) patients, respectively. At 6-month follow-up, significant improvements were seen across multiple validated questionnaire and strength measurement assessments. Median patient-reported improvement level was 7.0 on a 10-point Likert scale.DiscussionStudy patients demonstrated good understanding of PFMT/PFE and program completion was associated with significant improvements across a variety of subjective incontinence and quality of life outcomes, as well as objective strength testing.